Respuesta :
The correct answer is: [C]: " a = ± [tex] \sqrt{25 - b^2} [/tex] " .
___________________________________________________________
Explanation:
_________________________________________________________
We are given:
_________________________________________________________
→ " 25 = a² + b² " ; Solve for "a" ;
_________________________________________________________
→ To solve for "a" ; we want to isolate "a" on one side of the equation.
_________________________________________________________
We can rewrite: " 25 = a² + b² " ;
as: " a² + b² = 25 " .
_________________________________________________________
Then, we can subtract " b² " from each side of the equation; as follows:
_________________________________________________________
→ " a² + b² − b² = 25 − b² " ;
to get:
_________________________________________________________
→ " a² = 25 − b² " ;
_________________________________________________________
→ Now, take the square root of EACH SIDE of the equation ;
to isolate "a" on one side of the equation; & to solve for the value(s) of "a" ;
_________________________________________________________
→ √(a²) = [tex] \sqrt{25 - b^2}[/tex] ;
to get:
_____________________________________________________
→ a = | [tex] \sqrt{25 - b^2}[/tex] | ;
→ a = ± [tex] \sqrt{25 - b^2}[/tex] ;
→ which is: Answer choice: [C]: " a = ± [tex] \sqrt{25 - b^2}[/tex] " .
______________________________________________________
___________________________________________________________
Explanation:
_________________________________________________________
We are given:
_________________________________________________________
→ " 25 = a² + b² " ; Solve for "a" ;
_________________________________________________________
→ To solve for "a" ; we want to isolate "a" on one side of the equation.
_________________________________________________________
We can rewrite: " 25 = a² + b² " ;
as: " a² + b² = 25 " .
_________________________________________________________
Then, we can subtract " b² " from each side of the equation; as follows:
_________________________________________________________
→ " a² + b² − b² = 25 − b² " ;
to get:
_________________________________________________________
→ " a² = 25 − b² " ;
_________________________________________________________
→ Now, take the square root of EACH SIDE of the equation ;
to isolate "a" on one side of the equation; & to solve for the value(s) of "a" ;
_________________________________________________________
→ √(a²) = [tex] \sqrt{25 - b^2}[/tex] ;
to get:
_____________________________________________________
→ a = | [tex] \sqrt{25 - b^2}[/tex] | ;
→ a = ± [tex] \sqrt{25 - b^2}[/tex] ;
→ which is: Answer choice: [C]: " a = ± [tex] \sqrt{25 - b^2}[/tex] " .
______________________________________________________